Pengaruh Kombinasi Starter Kultur Lactobacillus plantarum dan Lactobacillus acidophillus terhadap Karakteristik Mikrobiologis dan Kimiwawi pada Minuman Fermentasi. - Syachroni; Fatma Maruddin; Farida Nur Yuliati; Andi Nurul Mukhlisah (Universitas Sulawesi Barat, 2020)
Lactobacillus plantarum and Lactobacillus acidophilus are a probiotic bacteria which can be combined as a starter fermentation products using fresh milk and reconstitution milk as a growth medium. The aim of this study was to determine the combined effect of L. plantarum and L. acidophilus on total bacteria, lactic acid, and pH levels were used as a starter culture fermented milk beverage. The study was designed using a completely randomized design (CRD) 3 treatments (a combination of 1:1, 1:2, and 2:1) with 5 replications. The results showed that the number of bacteria at the level of a combination of 1:1, 1:2, and 2:1 respectively were 8.96±5.80; 8.22±5.80 and 8.72±5.80 (log cfu/ml), lactic acid content were 0.36±0.008 %; 0.41±0.008 %; and 0.49±0.008 %, and the pH were 4.91±0.02; 4.67±0.02; and 4.54±0.02. The best combination of L. plantarum and L. acidophilus bacteria for fermented milk was 1:1 based on the growth activity of lactic acid bacteria and pH.